A Markov-Switching Model for Indian Stock Price and Volume. (December 2015) - Chaudhuri, Kausik; Kumar, Alok
Using weekly data from the Indian stock market, we examine the relationship between stock price and trading volume. Our framework is Markov Switching-Vector Error Correction Model (MS-VECM). We justify the use of nonlinear model using the Brock, Dechert and Scheinkman (BDS) test and the information criteria. The long-run dynamics are characterised by one cointegrating vector relating the price to trading volume. We find that stock price is weakly exogenous only in the high volatility regime. The MS-VECM with two regimes provides a good characterisation of the Indian stock market and performs well relative to the other linear and nonlinear models. JEL Classification: C32, G12, E32